Hardening AISI 316 Steel Using INTI Dense Plasma Focus Machine - Arwinder, Singh; Teh, Thiam Oun; Soi, Wei Xuan; Saw, Sor Heoh; Lee, Sing (AIP Publishing, 2023)
Surface modification of material has been an ongoing process since the iron age as can be observed in the process of making iron tools and weapons. Today the methods of material hardening have become much more varied and include nitriding, carburizing, boriding and various heat treatment. In this paper, a study on hardness improvement using nitriding on AISI 316 steel using INTI Plasma Focus Machine was carried out. The plasma dynamics was analysed with the aid of the Lee model code and it was found that the energy produced by the plasma focus machine was 4 Joules while 12 shots was needed to improve the hardness of the steel by 30% when the plasma focus was set at a pressure of 1 torr nitrogen gas and the sample was placed 40 mm from the anode tip.